Physical activity counseling by primary care physicians: attitudes, knowledge, implementation, and perceived success - Diehl, Katharina; Mayer, Manfred; Görig, Tatiana; Herr, Raphael; Schneider, Sven (Journal of physical activity and health, 2015)
Background: In physical activity (PA) counseling, primary care physicians (PCPs) play a key role because they are in regular contact with large sections of the population and are important contact people in all health-related issues. However, little is known about their attitudes, knowledge, and perceived success, as well as about factors associated with the implementation of PA counseling. Methods: We collected data from 4074 PCPs including information on physician and practice characteristics, attitudes toward cardiovascular disease (CVD) prevention, and measures used during routine practice to prevent CVD. Here, we followed widely the established 5 A’s strategy (Assess, Advise, Agree, Assist, Arrange). Results: The majority (87.2%) of PCPs rated their own level of competence in PA counseling as ‘high,’ while 52.3% rated their own capability to motivate patients to increase PA as ‘not good.’ Nine of ten PCPs routinely provided at least 1 measure of the modified 5 A’s strategy, while 9.5% routinely used all 5 intervention strategies. Conclusions: The positive attitude toward PA counseling among PCPs should be supported by other stakeholders in the field of prevention and health promotion. An example would be the reimbursement of health counseling services by compulsory health insurance, which would enable PCPs to invest more time in individualized health promotion.